2021
DOI: 10.1038/s41598-020-79657-5
|View full text |Cite
|
Sign up to set email alerts
|

Epidural analgesia does not impact recurrence or mortality in patients after rectal cancer resection

Abstract: The relationship between epidural analgesia and rectal cancer outcome is not fully clarified. We aimed to investigate the putative effect of epidural analgesia on the risks of recurrence and mortality after rectal tumour resection. In this monocentric cohort study, we consecutively enrolled patients with stage I–III rectal cancer who underwent tumour resection from 2005 to 2014. Patients received epidural analgesia or intravenous opioid-based analgesia for postoperative pain control. Primary endpoint was first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…In patients with rectal cancer resection (stage I–III), Wu et al . [ 34 ] concluded that postoperative EA also did not improve recurrence or mortality, with a follow-up duration of 46.1 months, when compared to opioid analgesia. A retrospective study by Exadaktylos et al .…”
Section: Discussionmentioning
confidence: 99%
“…In patients with rectal cancer resection (stage I–III), Wu et al . [ 34 ] concluded that postoperative EA also did not improve recurrence or mortality, with a follow-up duration of 46.1 months, when compared to opioid analgesia. A retrospective study by Exadaktylos et al .…”
Section: Discussionmentioning
confidence: 99%
“…49 Second, given that intraoperative blood loss and perioperative blood transfusion were linked to greater mortality rates after cancer surgery, strategies aimed at reducing blood loss and the use of blood transfusion during liver resection should be further developed, especially in cirrhotic liver. [33][34][35]50 Third, high-risk patients may need close observation and intensive care for possible bile leakage, infection, and organ failure after surgery. More studies are required to validate the efficacy of our model in reducing complications after liver resection.…”
Section: Discussionmentioning
confidence: 99%
“…Surgical and anesthetic covariates were extent of hepatectomy (>2 Couinaud liver segments or not), R0 resection, laparoscopic or robotic surgery, epidural anesthesia, intraoperative blood loss and transfusion, and anesthesia time. 22,30–35…”
Section: Methodsmentioning
confidence: 99%
“…However, higher level of preoperative carcinoembryonic antigen, perioperative blood transfusion, advanced cancer stage, and pathological lymphovascular invasion were independent risk factors for cancer recurrence and death in these patients ( 10 ). In patients with rectal cancer resection (stage I-III), postoperative EA also did not improve recurrence or mortality with a follow-up duration of 46.1 months when compared to opioids analgesia ( 11 ). For patients with stage IV colorectal cancer, one study involving 999 patients showed perioperative EA was not associated with better progression-free or overall survival after surgeries with 17.5 months follow-up ( 12 ).…”
Section: Effects Of Perioperative Ea On Certain Cancer Typesmentioning
confidence: 96%